Expanding Inclusivity with Learner-Generated Study Aids in Three Different Science Courses - Piontkivska, Helen; Gassensmith, Jeremiah J; Gallardo-Williams, Maria T (Journal of chemical education, 2021)
Note taking is a seemingly simple study strategy, yet as a source of learner-generated content its perceived effectiveness varies across subjects and from student to student, as not all students are able to create high-quality notes without guidance. While often advocated by the instructors, the use of notes as exam aids (whether used in open-books exams or not) is a pedagogical practice that has invited some controversy, but there are studies that justify the use of student-created reminder sheets by acknowledging that students must review the material in order to organize and create their study aids. Preparing for exams by actively developing formula sheets or other study aids assists students in studying, even if they are not consciously aware they are studying. We would like to suggest that modeling the process of creating successful study aids from class notes is an inclusive practice that leads to improved outcomes in low-performing students and increases their agency. Creating scaffolds for note taking, whether through sharing examples or prompting synthesis of information, allows for higher-quality note taking across all learners. We provide examples from three separate courses in which the instructors took this approach in widely different ways, and we offer a set of best practices for other instructors interested in using these resources in their own courses.